Studies on Pyrimidines, Part I: Synthesis and antibacterial Activity of 4-(2’-Hydroxy-5’-methylphen-1’-yl)-6-substituted-phenyl-1-,2,5,6-tetrahydroxpyrimidine-2-thione - Champaneri, H.R.; Modi, S.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Pyrimidine-2-thiones have been prepared by heating chalcones with thiourea in ethanolic potassium hydroxide. The antibacterial activities of the compounds have been determined.